Contribuciones de la historia ambiental para la sustentabilidad local. Estudio de los casos de los Oasis de Comondú, Baja California Sur, México (siglos XVIII-XXI) y de la Vega de Granada, España (siglos XIX-XX) - Cariño Olvera, Martha Micheline; Ortega Santos, Antonio (Revista de historia., 2014)
This article presents a comparative environmental historical research applied to the management of irrigated agroecosystems at Iberian Peninsula -province of Granada- and Baja California, Mexico. We describe the hydraulic systems, construction of agroecosystems and its adaptation to water availability and the establishment of comunal institutions that managed these territories and its resources, specially water. We also analyze how all this elements leaded to the creation of a local knowledge of biocultural heritage in both studied regions. This approach allows us to realize the capacity of this territories and communities to keep on generating local knowledge of agroecosystems management essential to design a sustainable future in vegas and oases.